The Parasitic Contamination of Edible Raw Vegetables in Karaj, Iran in 2017 - Aliehsan HEIDARI; Mahsa HEZAROSI; Ensieh NASSERKHAIL; Monireh SEZAVAR; Hossein KESHAVARZ; Amir BAIRAMI; Mohammad ZIBAEI; Kourosh KABIR (Tehran University of Medical Sciences, 2020)
No Abstract